(untitled) (World Science, 2023)
The objectives of the long-term development policy of Mongolia "VISION-2050" include scientific and knowledge-based development of agricultural production with the sight of sustainable development, the ability to transform knowledge into practice, the introduction of advanced technologies and innovations, the extension of agricultural raw materials and products in a foreign market, suspending the import of certain types of raw materials and products, and increasing exports. In order to determine the hardness of grain seeds, carried out 3-5 repeated experiments and measurements on the laboratory equipment for each grain grade after considering the different levels of moisture and made mathematical and statistical analysis on data of collected samples and processed experiment results.